The effect of workplace environment on employee’s learning and development / Sarah Sabir Ahmad ... [et al.] - Sabir Ahmad, Sarah; Wazir, Norsyuhada; Zakaria, Azfahanee; Mat Seman, Mhd Azmin (UiTM Cawangan Kedah, 2021)
Workplace environment plays a significant role in an organization. Most of the difficulties faced by employees are related to the workplace environment. The level of efficiency of employee’s learning and development can be augmented through developing a conducive working atmosphere in the organization. The objective of this study is to determine the relationship of the workplace environment on employee’s learning and development. The research was conducted at Penang Port Sdn. Bhd. A closed ended questionnaire using Google Form was adapted and established to get feedback from the target audience and SPSS was utilized for analysis to derive results from the collected data. From the Multiple Regression analysis, it was observed that two factors training and development and employee engagement has a relationship with employee’s learning and development. Therefore, it is suggested that enhancing the training, development and engaging employees in company activities are helpful in developing a working environment that has a positive impact on employee’s learning and development in the organizations.